Removal of Organic pollutant with the use of Rotating Biological Contactor. (2018) - Rana, Saraswati; Gupta, Nitish; Rana, R.S.
Abstract: This paper presents rotating biological contactor (RBC) method for the treatment of phenol containing effluents. The wastewater containg aromatic chemical structure, is most difficult to trat due to its stability and recalcitrant towards degradation. Physico-chemical treatment methods are costlier affairs because of comsumption of large quantity of chemicals production of sludge and use of sophisticated instruments. Thus, RBC is the biological methods which preferred due to simple, cheap, process stability and eco-friendly operations and also offers high interfacial area generated in the rotating disc to establish good contact between the microbial species and pollutants.. Treatment of synthetic wastewater containing phenol was studied in a Rotating Biological Contactor (RBC). Parameters such as Mixed liqure suspended solid (MLSS) concentration, hydraulic retention time (HRT), initial phenol concentration, disc submergence, rotation per minute (RPM) have been optimized to increase the phenol removal efficiencies. More than 56% phenol removal was obtained at optimum conditions of 1 g/l glucose and 250 mg/l of phenol concentration at 14hr retention time, 40% disc submergence and 30 rpm.